A Possible Involvement of Ion Transporter in Tumor Necrosis Factor α and Cycloheximide-Induced Apoptosis of Endothelial Cells. Issue Volume 8:Issue4/ 5(1999) (1999) - Fujita Fujita, Hiroshi Hiroshi; Morita Morita, Ikuo Ikuo; Murota Murota, Sei-itsu Sei-itsu
Abstract : We examined the tumor necrosis factor α (TNFα)-induced apoptosis of vascular endothelial cells from the standpoint of ion channels. Cultured vascular endothelial cells from bovine carotid artery were used. Apoptosis was determined by a propidium iodide assay. Treatment of the endothelial cells with TNFα and cycloheximide for 6h induced nuclear fragmentation in a TNFα dose-dependent manner (1-10 ng/ml). Concomitant treatment of endothelial cells with TNFα at a dose of 10ng/ml and cycloheximide at a dose of 10 micro g/ml elicited endothelial cell apoptosis as high as 23.4±4.1% at 6h after administration. However, 10 ng/ml TNFα alone elicited a little apoptosis at 6h after its administration (% apoptosis=4.1±0.8%). Cycloheximide (10 μg/ml) did not induce apoptosis at all. Concomitant treatment of endothelial cells with 1 m mol/l of 4, 4-diisothiocyanatostilbene-2, 2-disulfonic acid, which is a chloride bicarbonate exchanger blocker, partially inhibited the TNFα and cycloheximide-induced endothelial cell apoptosis. On the other hand, endothelial cell apoptosis due to TNFα and cycloheximide was completely inhibited by benzyloxycarbonyl-Asp-CH2 OC(O)-2, 6-dichlorobenzene (50 μmol/l), an inhibitor of caspase. Moreover, pyrrolidine dithiocarbanate, an inhibitor of nuclear factor kappa B (NF-κB), also suppressed endothelial cell apoptosis induced by TNFα and cycloheximide completely. These findings suggest that the endothelial cell apoptosis induced by TNFα and cycloheximide is closely related to not only chloride ions, but also both NF-κB and caspase activation. That is to say, there is a possibility that chloride ions or bicarbonate (pH) may play an important role in signal transduction such as NF-κB and caspase activation in the apoptosis induced by TNFα and cycloheximide.